Ultrasonic flexural mode emitters: New approaches to increasing sound pressure during oscillation generation in gas media - Vladimir Khmelev; Andrey Shalunov; Sergey Tsyganok; Alexandеr Sinkin; Pavel Danilov (PLoS ONE, 2025)
This work is devoted to the development and study of ultrasonic flexural-oscillating disk emitters for gas environments, generating elastic vibrations at ultrasonic frequencies (above 20 kHz) with high sound pressure levels required for energy-intensive technological processes (sound pressure levels exceeding 140 dB). The aim of the study was to identify the limitations of traditional flat disk designs and to substantiate new technical solutions that can significantly improve radiation efficiency in gas environments. The study demonstrated that the use of a flat titanium disk with a diameter of 146 mm, operating in the second bending mode, yields a sound pressure level of 147.5 dB (471 Pa), while the implementation of a stepped-profile surface of the same diameter increases the SPL to 153.2 dB (914 Pa). The subsequent use of phase-aligning horns and rear reflectors enabled a record-breaking sound pressure level of 159.2 dB (1824 Pa), more than double the original values and significantly exceeding the performance of known analogues. For comparison, speakers with stepped-profile disks with diameters of 250, 320, 360, and 410 mm, operating in the third, fourth, and higher vibration modes, were manufactured and tested. Despite the increase in radiating surface area, the achieved sound pressure levels were 140 dB (195 Pa), 143 dB (350 Pa), 148 dB (435 Pa), and 150 dB (700 Pa), respectively, which turned out to be lower than those of emitters with a diameter of 146 mm, operating in the second mode. The results confirm the feasibility of creating emitters operating specifically in the second flexural mode and demonstrate the advantages of stepped-profile disk geometry and phase-equalizing horn systems. The resulting solutions enable the generation of directional acoustic fields with pressure levels exceeding at minimum 155 dB and at maximum 159 dB. In turn, these techniques open up broad application prospects in air purification, aerosol precipitation, fire safety, and industrial drying and defoaming processes.